2021
DOI: 10.1371/journal.pone.0252191
|View full text |Cite
|
Sign up to set email alerts
|

Digital occlusal analysis of pre and post single posterior implant restoration delivery: A pilot study

Abstract: Objectives The purposes of this study were to analyze the effects of single posterior implant restorations delivery on the redistribution of bite force and to evaluate the changes in occlusal force distribution of prostheses and potential influencing factors on occlusion variation at different stages. Materials and methods Thirty-two single posterior restorations in 30 participants (18 women and 12 men aged 27 to 75 years) were placed into either a unilateral single-tooth defect (n = 17) or on either side of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
1
8
0
6
Order By: Relevance
“…Also, the change in mean MBF after two months was 133 N when compared to the baseline and 50 N when compared to the 24-hour readings. Similar findings that there is an increase in bite force after implant crowns were seen in a study by Zou et al [21], which showed an increase of only 3-6% but was statistically significant when statistics were done. It was 3.31% for a unilateral single posterior implant and 6.83% for a bilateral restoration.…”
Section: Discussionsupporting
confidence: 88%
“…Also, the change in mean MBF after two months was 133 N when compared to the baseline and 50 N when compared to the 24-hour readings. Similar findings that there is an increase in bite force after implant crowns were seen in a study by Zou et al [21], which showed an increase of only 3-6% but was statistically significant when statistics were done. It was 3.31% for a unilateral single posterior implant and 6.83% for a bilateral restoration.…”
Section: Discussionsupporting
confidence: 88%
“…The sample size is calculated according to the experimental research method ( Zhou et al, 2021 ), and the analysis index is “the change of occlusal force distribution before and after free end implant restoration”, assuming that the data to be measured is occlusal force, if the standard deviation of the difference in occlusal force of the subjects in this study is For σ = 3 units, every 2 units of occlusal force increase after implant restoration was considered meaningful, α was 0.05, and the test efficiency 1-β was 0.90. The standard deviation of the bite force of the sample is s=(σ = )3 units, δ = 2 units of bite force change, α = 0.05, Zα/2 = 1.96, β = 0.10, Zβ = 1.282.…”
Section: Methodsmentioning
confidence: 99%
“…El esmalte de los dientes se desgasta o fisura ante problemas oclusales, mientras que los materiales que confeccionan las prótesis no sufren ningún cambio ante sobrecargas. Todo esto hace que el diente pueda adaptarse mejor ante situaciones anómalas, mientras que le implante no posee dichos mecanismos de adaptación (21).…”
Section: Anatomía Y Fisiología Diferencias Entre El Implante Dental Y...unclassified
“…Debido a las diferencias anatómicas y fisiológicas comentadas en los apartados anteriores entre dientes e implantes, se hace necesario la construcción de un sistema oclusal independiente para este tipo de prótesis parciales implantosoportadas, de modo que se les pueda dotar de mecanismos de defensa ante las anormalidades oclusales que puedan surgir (19) (21).…”
Section: Teoría De La Oclusiónunclassified
See 1 more Smart Citation